Atmospheric paint materials for fast hardening - Gurina, Galina; Druzhynin, Yevhen; Kaplina, Katerina (BoScience Publisher, 2024)
A formulation of matte alkyd weather-resistant enamel of white color was developed for the successful creation of a technological process of manufacturing enamel for industry and design. The optimization of the technological process was carried out with the aim of energy and resource saving, and the technological parameters of the production of alkyd oligomer and enamel were determined. I will study the effect of a matting admixture based on a mixture of aerosol and calcium stearate on the physical and mechanical properties of low-gloss enamel coatings.
Keywords: alkyds; enamel; gloss; matting impurities; technological parameters; dispersion